2017
DOI: 10.1016/j.jalz.2017.07.161
|View full text |Cite
|
Sign up to set email alerts
|

[O2–04–01]: Clearance of Beta‐amyloid Is Facilitated by Apolipoprotein E and Circulating High‐density Lipoproteins in Bioengineered Human Vessels

Abstract: Amyloid plaques, consisting of deposited beta-amyloid (Ab), are a neuropathological hallmark of Alzheimer's Disease (AD). Cerebral vessels play a major role in AD, as Ab is cleared from the brain by pathways involving the cerebrovasculature, most AD patients have cerebrovascular amyloid (cerebral amyloid angiopathy (CAA), and cardiovascular risk factors increase dementia risk. Here we present a notable advance in vascular tissue engineering by generating the first functional 3-dimensioinal model of CAA in bioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Further, the model recapitulates the well‐established genetic effects of APOE on Aβ transport and accumulation. Suitability of this model for use in drug development was validated by investigating the beneficial effects of high density lipoprotein (HDL), which showed that HDL isolated from young healthy donors attenuated Aβ‐mediated EC activation and reduced CAA in the engineered vascular wall independent of APOE isoform 165,166 . These results show the promise of engineered human tissues as an experimental platform to investigate VCID mechanisms.…”
Section: Gaps In Knowledge and Research Opportunitiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, the model recapitulates the well‐established genetic effects of APOE on Aβ transport and accumulation. Suitability of this model for use in drug development was validated by investigating the beneficial effects of high density lipoprotein (HDL), which showed that HDL isolated from young healthy donors attenuated Aβ‐mediated EC activation and reduced CAA in the engineered vascular wall independent of APOE isoform 165,166 . These results show the promise of engineered human tissues as an experimental platform to investigate VCID mechanisms.…”
Section: Gaps In Knowledge and Research Opportunitiesmentioning
confidence: 95%
“…Recent advances using induced pluripotent stem cells (iPSC)‐derived neurons to form “brain in a dish” 3D cultures promise to fill an important niche between humans and animal models toward deciphering regulatory pathways and identifying therapeutic avenues for neurologic and psychiatric diseases 163,164 . The most advanced model of human CAA to date was created using scaffold‐directed 3D bioengineered vessels consisting of primary human ECs and human SMCs, cultured either without primary human astrocytes to mimic leptomeningeal arteries or with primary human astrocytes to mimic penetrating arteries 165,166 . The engineered vessel contains a tight BBB that separates “brain” from “blood” circulating through the vessel lumen.…”
Section: Gaps In Knowledge and Research Opportunitiesmentioning
confidence: 99%
“…Cardiovascular risk factors also increase the risk of dementia. Robert et al (Robert et al, 2017) used bioengineered human cerebral vessels to show that in that system, Apo E and circulating HDL mediate amyloid-beta transport and Apo E4 was less effective than Apo E2 in facilitating this transport.…”
Section: Apo E4 In Ad-associated Neurovascular Functionmentioning
confidence: 99%
“…Puromycin (1 mg/l) was added on D1 in fresh DMEM-F12/N2 + doxycycline medium for selection up to 48 hours. On D3, differentiating neurons were detached with 20 Accutase and re-plated on cultured mouse glia, MEFs, or just matrigel-coated 24-well plates (2x10 5…”
Section: Generation Of Human Neurons From H1 Human Es Cellsmentioning
confidence: 99%
“…First, it has been shown that ApoE is important for the clearance of amyloid-b (Ab) peptides, which in turn are thought to be central players in AD pathogenesis (17)(18)(19)(20). This observation suggests that ApoE4 promotes AD pathogenesis by increasing the concentration of pathogenic Ab, but the precise mechanisms involved remain uncertain, as does the actual role of Ab in AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%